Estimating the Consequences of Norway's National Scale-Up of Early Childhood Education and Care (Beginning in Infancy) for Early Language Skills. (February 2018) - Dearing, Eric; Zachrisson, Henrik Daae; Mykletun, Arnstein; Toppelberg, Claudio O.
While most early childhood education and care (ECEC) programs taken to scale in the United States have served socially disadvantaged 3- to 5-years-olds, Norway scaled up universal ECEC from age 1. We investigated the consequences of Norway's universal ECEC scale-up for children's early language skills, exploiting variation in ECEC coverage across birth cohorts and municipalities in a population-based sample (n = 63, 350). Estimates from two-stage least squares (i.e., instrumental variable) regression and generalized difference-in-differences models indicated the scale-up of universal ECEC led to improved language outcomes, particularly for low-income children. As preschool programs at scale become increasingly common in the United States, our results from Norway help inform debate about the merits of universal versus targeted policies and should provoke discussion about the benefits of beginning ECEC programs as early as infancy.